La mise en oeuvre législative des accords des partenaires sociaux européens : défis et débats - Jean-Paul Tricart (European Trade Union Institute (ETUI), 2019)
– This Working Paper analyses the development of the interpretation that the European Commission has given to the TFEU provision concerning mechanisms for extensions of collective agreements. The paper examines how the Commission has reinterpreted these provision and the challenges this poses for the social partners.
Keywords: 330; social partners; European labor law; EU social law; EU law; Sozialpartner; Europäisches Arbeitsrecht; EU-Sozialrecht; EU-Recht